Analisis Faktor-Faktor Yang Menjadi Penyebab Utama Anak-Anak di Desa Parumaan Kecamatan Alok Timur Putus Sekolah - Yusman Yusman; Abdullah Muis Kasim; Danar Aswim (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the main factors causing children in Perumaan Village, East Alok District to drop out of school, as well as the efforts made to overcome this problem. A descriptive qualitative method was used. This research was conducted in Parumaan Village, East Alok District, from February 12 to February 28, 2025, because there are still children who drop out of school in Parumaan Village. The data sources in this study are primary and secondary data sources. Data was obtained through in-depth interviews, field observations, and documentation. After collection, the data was analyzed following these steps: Data Collection, Data Reduction, Data Presentation, Conclusion Drawing, and Verification.The results of the study show that the main causes of children dropping out of school can be divided into two factors, namely internal and external. Internal factors include lack of parental attention, economic conditions, and low interest in learning among children. Meanwhile, external factors include an unsupportive social environment, the influence of promiscuity, and low levels of parental education. These findings show that children tend to lose their educational direction when support from their families and surrounding environment is minimal. To address this issue, several efforts have been made, such as raising awareness about the importance of education by the village government, providing economic assistance such as scholarships and KIP (Indonesian Smart Card), and involving the community through mutual cooperation and mentoring. This study recommends strengthening collaboration between families, schools, the government, and the community to create a conducive and sustainable educational environment.